MODEL PENGUJIAN PERATURAN PERUNDANG-UNDANGAN SATU ATAP MELALUI MAHKAMAH KONSTITUSI - Sholahuddin Al-Fatih (Faculty of Law, University of Muhammadiyah Malang, 2017)
Post-reform of the role of judicial institution is run by two institutions namely the Supreme Court and the Constitutional Court. The duties and authorities of the two institutions are regulated in the Constitution of the Republic of Indonesia 1945 and the act that addresses the three institutions more specifically. Several powers possessed by the Supreme Court and the Constitutional Court, one of them is the authority to judicial review. The Constitutional Court is authorized to review the act on the Constitution of the Republic of Indonesia 1945, while the Supreme Court is authorized to review under the Act on the above legislation.The unfairness of the regulatory testing function is feared to trigger bureaucratic inefficiency. Based on data released by the Supreme Court Clerk, it was recorded during 2016 that the Supreme Court received 18,514 cases, including the Hak Uji Materi (HUM) subject to legislation under the Act. While the number of cases of judicial review of the Constitutional Court in 2016-2017 amounted to only 332 cases. Therefore, it is necessary to conduct a bureaucratic reform and provide new ideas related to the model of one court of judicial review in Indonesia. So that in this paper will be discussed deeply about problematic of judicial review in Indonesia and the authority of the Constitutional Court to review the act under one roof with SIJURI mechanism.